Komputasi Numerik Berkinerja Tinggi dari Integral Multidimensi Menggunakan Sampel Acak - Widjaja, Andreas; Gautama, Tjatur Kandaga; Sujadi, Sendy Ferdian; Wijaya, Bernadus Indra (Maranatha University Press, 2025)
This study examines the use of high-performance computing to carry out multidimensional integral calculation based on stochastic techniques, particularly in the context of Monte Carlo integration. Considering that traditional methods are facing extreme difficulty especially in high-dimension when encountered with